Attending to Methodological Challenges in Qualitative Research to Foster Participation of Individuals with Chronic Critical Illness and Communication Impairments - Fuchsia Howard; Sarah Crowe; Scott Beck; Gregory Haljan (SAGE Publishing, 2021)
Individuals with chronic critical illness experience multiple complex physiological disturbances including ongoing respiratory failure, requiring prolonged mechanical ventilation, and thus communication impairments. In conducting a qualitative interpretive description study, we sought to ensure that individuals with chronic critical illness themselves were included as participants. Our commitment to recruiting these individuals to the study and ensuring their data meaningfully informed the analysis and findings required us to reconsider and challenge some of the traditional notions of high-quality qualitative research and develop appropriate practical strategies. These strategies included: (1) centering participant abilities and preferences, (2) adopting a flexible approach to conducting interviews, (3) engaging in a therapeutic relationship, and (4) valuing "thin" data. In this article, we extend existing literature describing the complexities of conducting research with individuals with communication impairments and strategies to consider in the hopes of informing future research with other populations historically excluded from study participation.